Trainee primary-school teachers’ perceptions on CLIL instruction and assessment in universities: A case study - Gómez, María Victoria Guadamillas (Acta Scientiarum. Education, 2016)
CLIL is an important approach in training future Primary School Teachers since bilingual programs developed at schools in Spain require not only professionals with proficientSecond Language (L2) levels, but also future teachers who are versed in the main methodological principles for CLIL. Firstly, this case study reviews the legislation for bilingual programs in Spain. Secondly, it describes teacher training through a CLIL course within the Faculty of Education at the University of Castilla-La Mancha, focussing on the methodology and evaluation procedures followed in the course. Thirdly, this paperrefersto the method performed to evaluate students’ perceptions ofthe CLIL training and assessment process. Finally, it shows the results from the study and some conclusionsrelated to the assessment and instruction process for the implementation of the CLIL approach in Primary School Teaching Undergraduate Programs.